Controversia de roles en investigación suplementaria y el principio de autonomía constitucional en la fase intermedia en el poder judicial Iquitos 2019 - Bardales Vasquez, Liliana (2024)
The work was developed in the city of Iquitos in the atmospheres of the Judicial Power of Loreto, the objective was to determine the circumstances in that controversy of lists is generated in the supplementary investigation and the principle of constitutional autonomy in the Judicial Power in the intermediate phase of the penal process, the study taken from three perspectives. The first one from the study point being this quantitative investigation, the you-gundo from the perspective of their purpose being basic in a first mo-mentions and then applied and the third from the descriptive study level former-plicativa, the population was conformed by the lawyers of the judicial power and the sample was constituted by the 63 right professionals. You arrive-rum to the conclusions: to. controversy of lists doesn't exist in the supplementary investigation and the principle of constitutional autonomy in the phase interme day in the Judicial Power of Loreto, b. He Articulates 346 numeral 5 are not In constitutional and the serious Diffuse Control the Artificial tool through which the irrelevancy would be determined or Not of the I Articulate 346 numeral 5, c. The Judges don't harm the principle of impartiality in the intermediate phase, neither neither they harm the attribution of strategist of the investigation that has the District attorney, d. it is viable that the Judge rises in consultation the order of so-breseimiento of the District attorney if discrepancy exists with such a decision and d. The hipóte-sis outlined work presently is rejected and the Alternating one is accepted controversy of lists since it doesn't exist in the supplementary investigation and the principles of autonomy in the Judicial Power of Loreto in the phase interme-day of the Penal Process.